Physiological and physical quality of local Araucaria angustifolia seed variety - Shibata, Marilia; Coelho, Cileide Maria Medeiros; Araldi, Cristhyane Garcia; Adan, Natalia; Peroni, Nivaldo (Acta Scientiarum. Agronomy, 2016)
Araucaria angustifolia seeds are the basis for the rural economy in southern Brazil, and the species presents different botanical varieties. The objective of this work was to evaluate the diversity of physical, physiological and biochemical characteristics of Araucaria angustifolia seeds from local varieties: ‘sancti josephi’, ‘angustifolia’, ‘caiova’, and ‘indehiscens’. Seeds were collected from the cities of Painel and Urubici in Santa Catarina State and tested for moisture content, 1000-seed weight, emergence, emergence speed index (ESI), root and shoot length, electrical conductivity, tetrazolium, soluble carbohydrates, and starch content. Among the varieties cited above, the angustifolia variety from Painel displayed a greater 1000-seed weight, ESI, electrical conductivity and shoot length. However, the sancti josephi variety displayed a lower emergence percentage, 1000-seed weight, ESI, root and shoot length, and carbohydrate content. In a cluster analysis, based on Euclidean distance, three groups constituting the sancti josephi, indehiscens, and caiova/angustifolia varieties were found. In conclusion, there is great diversity in A. angustifolia seeds. The angustifolia and caiova varieties displayed similar diversity, and their physiological quality was better than that of other varieties. Variety characterization allowed for the compilation of information regarding seed collection and use for seedling production and species conservation.